Solvent extraction of copper (II) from aqueous solutions by new organic reagent 2-[(3-Hydroxy phenyl)azo]-4,5- diphenyl imidazole - et.al, Shawket K. Jawad (Al-Qadisiyah Journal of Pure Science, 2017)
This study include synthesis of new organic reagent 2-[(3-Hydroxy phenyl)azo]-4,5-diphenyl imidazole (3-HPADPI) and used it as complexing agent for extraction of Cu2+ ion from aqueous solutions. The results show the optimum pHex=8, optimum concentration of Cu2+ ion was 40Î¼g in 5mL aqueous phase and the optimum shaking time was 10min. Stoichiometry study illustrated the complex structure was 1:1 Cu2+:(3-HPADPI). Effect of cations interferences was studied. Synergism effect show MIBK gave increasing of distribution ratio (D). The study of organic solvents effect appear there is not any linear relation between dielectric constant (Îµ) of organic solvents used and distribution ratio (D). Thermodynamically appear that the reaction was Endothermic reaction with Î”Hex=0.000062 KJ.mole-1, Î”Gex=-51.46 KJ.mole-1, Î”Sex= 159.31 J.mol-1.K-1.